The RootChip: an integrated microfluidic chip for plant science - Großmann, Guido (The plant cell, 2011)
Studying development and physiology of growing roots is challenging due to limitations regarding cellular and subcellular analysis under controlled environmental conditions. We describe a microfluidic chip platform, called RootChip, that integrates live-cell imaging of growth and metabolism of Arabidopsis thaliana roots with rapid modulation of environmental conditions. The RootChip has separate chambers for individual regulation of the microenvironment of multiple roots from multiple seedlings in parallel. We demonstrate the utility of The RootChip by monitoring time-resolved growth and cytosolic sugar levels at subcellular resolution in plants by a genetically encoded fluorescence sensor for glucose and galactose. The RootChip can be modified for use with roots from other plant species by adapting the chamber geometry and facilitates the systematic analysis of root growth and metabolism from multiple seedlings, paving the way for large-scale phenotyping of root metabolism and signaling.